Saprophytic fungi on tomato phylloplane: Effect of fungicides and leaf position on abundance, composition and diversity - Mónaco, Cecilia Inés (2001)
Fungal isolations were made from leaves of tomato plants cultivated in greenhouses in an area close to La Plata, Argentina. Three different schemes of fungicide application were evaluated: high frequency preventive sprayings (Commercial Greenhouse I), low frequency preventive applications (Commercial Greenhouse II) and no fungicide spraying (Control Greenhouse). Leaves were sampled immediately after second fruit formation from three levels of the foliage: low, medium and high. Plating dilution was used to isolate fungal species. Total c.f.u. number and species composition and diversity were assessed by the plating dilution technique. Fungal populations were most abundant on leaves from lower parts of the foliage in the Control Greenhouse. Diversity varied according to fungicide application frequency and leaf position in the canopy. Higher values were recorded for lower leaves in the Control Greenhouse compared with upper leaves from Commercial Greenhouse II. Likewise position in the canopy influenced the frequency of some species. The implications for natural biological control are discussed.